Analysis of Management Strategy in Facing Competitors at Horison Hotels Group - Royani, Solihin; Sonjaya, Aji; Awaludin, Revan Bilal; Lesmana, Dede Kiki; Musyaffa, Athallah Naufal (Journal of Bussines Management Basic, 2025)
This study aims to determine the management strategy in facing competitors at Horison Hotel Group. The data used in this study were obtained through the company's official website using digital research methods and qualitative case studies. The results of this test show that facing competitors in the hospitality industry is done through an approach that combines international standards with local cultural richness, including creating a unique and authentic hospitality experience.